Advanced Glaucoma as A Late Manifestation of Axenfeld-Rieger Syndrome - Olly Congga; Noor Syamsu; Noro Waspodo; Andi Tenrisanna Devi; Marliyanti Nurrahma Akib (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: To report a case of advanced glaucoma manifestation in Axenfeld-Rieger syndrome.Case Illustration: A 9 years old girl presented to our outpatient clinic with blurred vision in both eyesexperienced since the last 3 years. According to her labor history, she was born normal, full-term, birthweight is unknown. History of protruding eyes felt since last 1 year. History of previous treatment inSinjai given timolol 0.5% drop twice daily in both eyes 2 weeks ago. For ophthalmology examination,we performed visual acuity examination, orthopthic examination, Perkins tonometry, slit-lamp biomicorscopy, gonioscopy, funduscopy, biometry, B-scan ultrasonography, and Hertel mirror exophthalmometer measurement.Conclusion: Abnormalities of the angle may be found in patients with a diagnosis of Axenfeld-Riegersyndrome. These conditions are all associated with increased intraocular pressure and an icreasedincidence of glaucoma with around 50% of patients developing glaucoma. Early treatment will givebetter visual outcomes and good prognosis to Axenfeld-Rieger syndrome.Keywords: Axenfeld-Rieger syndrome, glaucoma